MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK AUTIS - DEA UNTARI, INTAN (Jurnal Pendidikan Khusus, 2017)
Abstract : Problem experienced by children with autism is less able to recognize the symbol of the number 1-10. Appropriate learning model used is the model of learning picture and picture. The model of learning picture and picture is a learning strategy that uses images as a media of learning. The purpose of this study to prove the influence of the model of learning picture and picture on the ability to recognize the symbol of the number of children with autism. This research method is quantitative with One Group research design, pretest, post test design. The results showed pretest mean values ??of 36.66  given 6 treatments in the aspect of sorting the symbols of numbers 1-10, pair the symbols of the numbers 1-10 with the number of real objects and pair the symbols of numbers 1-10 according to the number of images, and the average post-test score of 86.66. This is evidenced by the results of data analysis shows the value of z arithmet = 2.20 greater than the value of z table = 1.96. It can be concluded that the model of learning picture and picture has an effect on the ability to recognize the symbol of the number of children with autism   Keywords: Symbol of Numbers, Picture and Picture.